EVALUASI KESESUAIAN LAHAN PADI SAWAH, PANGAN LAHAN KERING DAN TANAMAN TAHUNAN SUB DAS MALANGGA DESA TINIGI KECAMATAN GALANG KABUPATEN TOLITOLI - Ansar, Ansari (JSTT, 2014)
An research was conducted to know the land suitability for paddy plant, food crop dry land, and annual plant in Malangga Sub Watershed, Tinigi Village, Galang Subdistrict, and the aim of the research also to minimize constraint and maximize potency for the increasing of productivity to develop agriculture sustainibility, and to evaluate the working of Malangga Sub Watershed, Tinigi Village, Galang Subdistrict. The research was conducted on April until June 2012. The research was an descritive research (non experiment), the data was collected on land suitability evaluation research of some comodity in Malangga Sub Watershed, Tinigi Village, Galang Subdistrict, Tolitoli Regency. The result of the research showed that the level of soil fertility in research area, as general, was low until medium. The research also showed that the land class was suitable for paddy plant of 403,84 ha, for food crop dry land was 94,38 ha, and for annual plant waas 548,4 ha. Economically evaluation showed that paddy plant was very suitable to be developed with R/C ratio was 1.8.Â  Â Â